Surge in the Red Tide: Rise of Maoist Militancy in India - Sujoyini Mandal (2016)
For eight long months prior to June 2009, members of the Communist Party of India- Maoist (CPI-M) ran a parallel government in Lalgarh, West Bengal with 1,100 villages under their control. Following their expulsion by paramilitary forces in an insurgency war, a formal ban has been imposed on the Maoists. Is India prepared to fight a long war?